Soft skills and the direction of the teaching-learning process of teachers in an educational institution in the district of Ate-Lima (GnosisWisdom, 2024)
The research: Soft skills and teaching-learning of teachers of the Educational Institution; The objective was to determine the correlation that exists between soft skills and the teaching-learning process of the teachers of the Educational Institution - Ate, with a quantitative approach, of a basic type, with a non-experimental, descriptive, transversal design and correlational. The population of 50 secondary level teachers, sample of 32 teachers between men and women, non-probabilistic selection. The technique was the survey with the soft skills questionnaire instrument and the teachers' self-assessment teaching-learning questionnaire, validated by expert judgment and reliable using the Cronbach's Alpha coefficient. The results in accordance with the objectives show 93.75% of the teachers an adequate soft skill and 87.5% show an outstanding direction of the teaching-learning process. The inferential statistical analysis accepts the hypothesis raised with a p value of 0.000 < 0.05 at a confidence level of 0.01, which indicates that there is a significant correlation between soft skills and the teaching process and by the r statistic of Pearson with the score of 0.795 states that the correlation is strong positive. The analysis by dimensions with the values for Pearson's r 0.723**; 0.707**; 0.684**and 0.666 indicate a significant correlation between empathy, teamwork, assertive communication, leadership and motivation with the teaching and learning of teachers, with a significance of 0.01, therefore, the null hypothesis was rejected and the hypothesis was retained alternates in all cases
Keywords: Soft skills; empathy; teamwork; assertive communication; leadership; motivation; teaching-learning